The Effectiveness of Ruspin Implementation in Supporting Community-Based Housing for Low-Income Communities Case Study: “Seguyub Rusunawa” Community Housing, Kedungcino, Jepara - Manaf, Asnawi; Rindu, Lathifa Salma (Department of Urban and Regional Planning, Universitas Diponegoro, 2026)
One of the primary challenges in housing management is ensuring every individual can access basic needs in the form of decent housing, particularly for Low-Income Communities (MBR). The Indonesian government developed the Self-Help Housing Stimulant Assistance (BSPS) program by applying RUSPIN (Rumah Unggul Sistem Panel Instan) technology, which is designed using a modular system to suppress costs and remain adaptive to the needs of residents. This study aims to evaluate the effectiveness of RUSPIN implementation at the “Seguyub Rusunawa” Community Housing in fulfilling the need for decent and affordable housing for MBR built through community-based self-help, reviewed from physical, economic, and social aspects.This study combines qualitative and quantitative methods (mixed method) with data collection in the form of structured in-depth interviews and observations. Interviews were conducted with one informant from the Jepara Regency Housing and Settlement Agency (Disperkim) and with 31 original beneficiaries residing in occupied units at Seguyub Rusunawa Housing, Kedungcino, Jepara. Meanwhile, observations were conducted by observing field conditions of the BSPS program implementation outputs applying the RUSPIN technology. The data obtained were analyzed through scoring and then interpreted descriptively, supported by the results of field observations regarding the physical conditions and the housing environment.Data analysis shows that the program feasibility variable has a percentage of 66.98% or effective, while the product (output) feasibility variable shows a percentage of 70.67% or effective. Meanwhile, the resource variable has a lower percentage than the other two variables, at 58.36% or quite effective. Overall, the implementation of RUSPIN at Seguyub Rusunawa Housing, Kedungcino, Jepara is effective in meeting the needs of MBR for decent and affordable houses, with an effectiveness level of 65.34%. Nevertheless, this percentage is at the lower limit and can still be improved. Additionally, this study also found that the resource aspect, which includes beneficiary self-reliance, building materials, supervision time, and labor, remains the main constraint in continuing independent house construction.